أسلوب وضع الإظهار موضع الإضمار- أسراره وأغراضه في القرآن الكريم: The style of showing in a position of hiding - its secrets and purposes in the holly Quran (Khairulummah, 2023)
This research paper addresses the phenomenon of showing ( الظاهر) in a position of hidingالإضمار) ( in the Holy Qur’an through an Rhetorical and analytical study. It is a pure rhetorical study which concluded that the the term showing in a position of hiding(وضع الظاهر موضع المضمر) is a prominent linguistic phenomenon of Arabic language  and especially the Holy Qur’an.This research aims to investigate the verses in holy Quran in that contain on showing in a position of hiding(وضع الظاهر موضع المضمر) and its purposes of its use in the  holy Qur´an, and describe the content of educational values that can be utilized and applied in daily life.The conclusion of this study is that Faith and aqidah education is a basic education in  the holy Quran. Delivered through several stories of the Messengers of Allah conveyed the message of tawheed to their people with patience.